2015
DOI: 10.1016/j.carj.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diagnostic Imaging Wait Times on the Prognosis of Lung Cancer

Abstract: Delays in patient flow through diagnostic imaging resulted in an increase in tumour size and stage, with a negative impact on prognosis of NSCLC. This information contributed to the hiring of additional CT technologists and extended CT hours to decrease the wait time for diagnostic imaging. With reduced wait times, the prognosis of NSCLC was not adversely impacted as patients navigated through diagnostic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Delays in beginning therapy for lung cancer may result in disease progression and death [4, 2427]. In one small study of patients with stage III cancers slated for definitive radiotherapy, treatment intent changed from curative to palliative in 29% owing to cancer progression in less than 30 days [25].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays in beginning therapy for lung cancer may result in disease progression and death [4, 2427]. In one small study of patients with stage III cancers slated for definitive radiotherapy, treatment intent changed from curative to palliative in 29% owing to cancer progression in less than 30 days [25].…”
Section: Commentmentioning
confidence: 99%
“…Stage progression is associated with decreased surgical cure rates and poorer overall survival [2]. Delays in the diagnosis and treatment of lung nodules are common [3, 4], and the timely care of lung nodules suspicious for cancer is presumed critical for individual patients and population health [5, 6]. Researchers have examined the impact of delays in lung cancer resection for more than 2 decades [7] We know that, as a group, patients with larger tumors do worse than patients with smaller tumors [8].…”
mentioning
confidence: 99%
“…However, the effect of timely investigation and treatment for lung cancer on progression-free survival (pfs), relapse-free survival (rfs) after primary surgical resection, and overall survival (os) is unclear 10,11 . Delays in patient flow through diagnostic imaging and biopsy, and prolonged times from diagnosis to radical radiotherapy have been reported by some authors to result in an increase in tumour size and stage 12,13 . Others have reported no association between time to diagnosis or treatment and clinical outcomes 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Byrne and co-workers report the change in stage between first abnormal imaging and CT-guided biopsy for 66 patients. 34 Over a median of 81 days, 17 patients progressed one stage, 5 progressed two stages and 1 progressed three stages. We assumed that patients receiving a false negative diagnosis would present 104 days later at an emergency department, at which point the proportion of patients progressing one or more stages would be as reported in Byrne et al where progression indicated stage beyond IV patients were assumed to remain at stage IV.…”
Section: Data Sourcesmentioning
confidence: 99%